(untitled) (Journal of Engineering, 2015)
In the present work effect of recycled heating and cooling on the values of concrete compressive strength due to high temperature of 4000C was studied. The tests show that the percent of reduction in compressive strength of the samples which exposed to a temperature of 4000C for one cycle was 32.5%, while the reduction was 52.7% for the samples which were exposed to recycled heating and cooling of ten times . Moreover a study of the effect of specimen sizes on the percentages of compressive strength reduction due to high temperatures (250, 500, 7500C) with the variation of cub’s size (100, 150, 200 mm) was studied. The tests show that the rate of reduction in compressive strength increases with increasing the exposed temperatures, but, the rate of reduction was decreased as the specimen size was increased.